2012
DOI: 10.4236/fns.2012.38154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rice (<i>Oryza sativa</i> L.) Added to Meju (Korean Soybean Koji) Dough on Variation of Nutritional Ingredients and Bacterial Community Diversity in Doenjang (Korean Soybean Paste)

Abstract: In this study, effect of rice added to meju dough was evaluated based on the variation of nutritional ingredients and bacterial community diversity in finished doenjang. The ratio of rice added to meju dough (cooked and crushed soybean before fermentation) was 0, 0.2, and 0.4 based on dry weight. Free amino acids, minerals, polyphenol, and total phenolic compounds relatively decreased by addition of rice. However, 2,2-diphenyl-1-picrylhydrazyl free radical (DPPH) scavenging and ferric ion reduction activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Similar findings were observed for reducing power capacity of Stryphnodendron adstringens leaf extracts (dos Santos Filho, Ferreira, & Paiva Gouvea, 2011). Jeon and Park (2012) also confirmed significant antioxidant activities in Doenjang samples and reported that antioxidants in Doenjang may function as protective agents against deterioration of quality due to oxidation reactions. Lower absorbance values indicate lower reducing power ability, whereas higher values indicate higher ability.…”
Section: Reducing Power Abilitysupporting
confidence: 90%
“…Similar findings were observed for reducing power capacity of Stryphnodendron adstringens leaf extracts (dos Santos Filho, Ferreira, & Paiva Gouvea, 2011). Jeon and Park (2012) also confirmed significant antioxidant activities in Doenjang samples and reported that antioxidants in Doenjang may function as protective agents against deterioration of quality due to oxidation reactions. Lower absorbance values indicate lower reducing power ability, whereas higher values indicate higher ability.…”
Section: Reducing Power Abilitysupporting
confidence: 90%